Case Study: Qayz Holdings (M) Sdn Bhd - Hakim, A.; Mohamed, Z. A. (Universiti Sains Islam Malaysia, 2024)
This case is about a few small business enterprises in the construction industry that were operating in one of the district in Selangor. In their regular acquaintance in the district, the five owners decided to jointly set up a holding company, with 5 subsidiaries, and the fifth one being the new brick manufacturing plant (churning out interlocking bricks). Most of them had not being formally trained in business. They faced some difficulties in the management of a holding company where they had to be more aware of what is required of being Board members and managing the subsidiaries. They are now jointly responsible not only for their own subsidiary but also the others under the Holding structure. With the new interlocking brick manufacturing factory, life had become a bit more challenging and this case reflects the difficulty of working as board members and managing the 5 subsidiaries. While they had climbed into a higher level of technology usage (IBS as compared to the normal brick and mortar technology), their management was still individualistic in nature and this case will demonstrate these common weaknesses through the financial problems that they had to endure.